Association of liver and renal function impairment with major cardiac events in heart failure patients (Annals of Medical Research, 2023)
Aim: We aimed to show whether liver and renal function tests impairment have an effect on cardiovascular major adverse events (MACE) in patients with chronic heart failure (CHF).Materials and Method: 514 Patients with Ejection Fraction (EF)